A DECADE OF THE PENTAHELIX APPROACH IN PUBLIC ADMINISTRATION: A BIBLIOMETRIC ANALYSIS - Yuni Indah Supriyanti; Hartuti Purnaweni; Wijayanto Wijayanto (Natapraja, 2026)
While the Pentahelix approach has been growing in the literature of collaborative governance, no systematic literature overview exists to portraying its conceptual progressions, thematic trends, and methodological patterns. This study aim to provides an overview of its development between 2015 and 2025 through a bibliometric analysis of 73 Scopus-indexed publications. The findings indicate that Indonesia a key driver in advancing the pentahelix approach. The model’s application spread beyond conventional administrative settings encompass sustainability initiatives, tourism environmental management, and business innovation. However, it should be noted that the qualitative case studies continue to dominate research. This approach has little use quantitative or mixed-method and data-driven techniques like social network analysis and so artificial intelligence. Moreover, the analysis show that a dearth of across national and across sectors, comparative studies as well as of integration of urgent strategic especially digitalization and the circular economy. These gaps created robust advanced frameworks such as Pentahelix 4.0 and 5.0, incorporate digital technologies and big data as promoters of policy innovation. This paper emphasizes the value of interdisciplinary and empirically robust research to ensure that the pentahelix model can effectively promote strategic collaboration, innovation, and sustainable public governance.